USE OF SCRIBING AND SKETCHNOTING TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Olha Myagkova (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article is devoted to the use of scribing and sketching technologies in the educational process as visualization technologies. It is proved that in the conditions of total environment with modern information technologies and large information flows and formation of clip thinking in students, visualization that takes into account these cognitive features promotes understanding, mastering and memorization of educational material, improves learning and communication skills, increases motivation, learning, and promotes critical thinking; keeps the attention of the individual on key points, makes him an active participant in the educational process. The advantages and disadvantages of using scribing technologies in the educational process are summarized. The types of scribing and possible variants of their use are researched and analyzed. Among them are painted, application, magnetic, flannel, which involves the use of flannel (carpet linograph). technologies for using special programs or online services to create online scribing (computer, animation, video scribing) is emphasised. Scribbing facilitation is singled out, which involves the translation of information from verbal to visual form. Attention is paid to the study of the positive impact of visualization on the assimilation and comprehension of material through sketching technologies: they increase student involvement in learning, encourage more effective strategies and promote key skills, including creative thinking, communication and skills to build and present knowledge. The main models of sketchouting and their variants of use are investigated: linear, vertical, radial, modular, trajectory, skyscrapers or columnar, popcorn.